2021
DOI: 10.1093/neuonc/noab141
|View full text |Cite
|
Sign up to set email alerts
|

The use of external control data for predictions and futility interim analyses in clinical trials

Abstract: Purpose External control data from completed clinical trials and electronic health records can be valuable for the design and analysis of future clinical trials. We discuss the use of external control data for early stopping decisions in randomized clinical trials (RCTs). Methods We specify interim analyses (IAs) approaches for RCTs, which allow investigators to integrate external data into early futility stopping decisions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…The increasing availability of patient-level data from completed clinical studies and electronic health records constitutes an opportunity for the development of novel trial designs that leverage EC data 5 , 7 , 9 , 15 , 18 . Recent contributions 5 , 8 , 18 have proposed methodologies to integrate EC data into the analysis of single-arm trials (ECTs). These methods replace published estimates of the SOC’s efficacy used as a benchmark with patient-level EC data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing availability of patient-level data from completed clinical studies and electronic health records constitutes an opportunity for the development of novel trial designs that leverage EC data 5 , 7 , 9 , 15 , 18 . Recent contributions 5 , 8 , 18 have proposed methodologies to integrate EC data into the analysis of single-arm trials (ECTs). These methods replace published estimates of the SOC’s efficacy used as a benchmark with patient-level EC data.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of EC data in the design and analysis of clinical trials can take several forms, including testing/estimating treatment effects upon study completion 5 , sample size re-estimation at interim analyses (IAs), and early decisions to terminate the study for futility or efficacy 7 , 8 . With the increasing availability of data from past trials, the prospective use of EC data in the design, conduct, and analysis of clinical trials has the potential to reduce the cost and time of evaluating new treatments 6 , 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The increasing availability of patient-level data from completed clinical studies and electronic health records constitutes an opportunity for the development of novel trial designs that leverage EC data 7,9,15,17,19 . Recent contributions 8,17,19 have proposed methodologies to integrate EC data into the analysis of single-arm trials (ECTs). These methods replace published estimates of the SOC's e cacy used as a benchmark with patient-level EC data.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses based on model-based simulations (Table 2) and in silico trials obtained by resampling the GBM datasets 8 (Table 3) indicated potential e ciency gains of HTs compared to RCTs when EC data without substantial limitations are available. We showed improvements of power, average study duration, and sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation